2014
DOI: 10.1097/iae.0b013e31829f7415
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Genetic Factors in Uveitis and Their Clinical Significance

Abstract: Multiple genetic factors play important roles in the pathogenesis of uveitis and may influence the clinical course of uveitis. Further studies to investigate the genetic mechanisms of uveitis might identify additional genetic associations and might have the potential for identifying novel therapeutic targets in the treatment of intraocular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 107 publications
(89 reference statements)
0
16
0
Order By: Relevance
“…15 Current anti-VEGF therapies delivered intravitreally include ranibizumab and aflibercept, as well as off-label bevacizumab. A main functional difference between aflibercept and other anti-VEGF agents is blockage of VEGF-B, PGF1, and PGF-2 in addition to VEGF-A isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…15 Current anti-VEGF therapies delivered intravitreally include ranibizumab and aflibercept, as well as off-label bevacizumab. A main functional difference between aflibercept and other anti-VEGF agents is blockage of VEGF-B, PGF1, and PGF-2 in addition to VEGF-A isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the MHC, several genes encoding for cytokines, chemokines, or immunoregulatory proteins have been assessed with respect to their participations in the pathogenesis of BD, but results obtained were inconsistent [51, 133, 134]. Two recent GWAS reports from Turkey and Japan and their additional meta-analyses which included cohorts from Europe, Middle East, and Korea revealed consistent and significant associations between the IL-10 and IL-23R/IL-12RB2 genes and BD [109, 114].…”
Section: Genetic Mechanisms Of Susceptibility To Behçet's Uveitismentioning
confidence: 99%
“…3 The exact pathogenesis of AAU is still unclear, but accumulating evidence has demonstrated that the disease is immune mediated and influenced by various endogenous factors. 4,5 For instance, studies have shown that singlenucleotide polymorphisms (SNPs) in TNF and their associated receptors are associated with AAU. 6 The levels of CCL2, CCL5, and their receptors have also been found to be significantly correlated with the severity of inflammation in AAU patients.…”
Section: Introductionmentioning
confidence: 99%